2020
DOI: 10.1177/0020720920940605
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Artificial ecosystem-based optimization for optimal tuning of robust PID controllers in AVR systems with limited value of excitation voltage

Abstract: This paper presents an application of a novel optimization method called Artificial Ecosystem-Based Optimization (AEO) to determine the optimal design parameters of the proportional-integral-derivative (PID) controller for an automatic voltage regulator (AVR) system. Unlike the previous studies presented in the literature, the proposed method takes into account the excitation voltage limit and therefore formulates a new objective function for optimal PID parameters design. The practical aspect of the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
0
25
0
1
Order By: Relevance
“…This paper takes the opening of mental health education courses in several local universities as the research object, including undergraduate, specialized and independent institutions. 16 The results showed that the scores of anxiety and terror of college students were significantly higher than the national norm, and the number and proportion of students scoring more than two points in the three factors of anxiety, compulsion and terror ranked the top three. This indicates that during the outbreak of new coronary pneumonia, college students are prone to psychological distress such as anxiety, compulsion and terror, especially in anxiety and terror.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…This paper takes the opening of mental health education courses in several local universities as the research object, including undergraduate, specialized and independent institutions. 16 The results showed that the scores of anxiety and terror of college students were significantly higher than the national norm, and the number and proportion of students scoring more than two points in the three factors of anxiety, compulsion and terror ranked the top three. This indicates that during the outbreak of new coronary pneumonia, college students are prone to psychological distress such as anxiety, compulsion and terror, especially in anxiety and terror.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…In the previous table, KA, KE, KG, and KS stand for gains of an amplifier, exciter, generator, and sensor, respectively, while TA, TE, TG, and TS are time constants of the amplifier, exciter, generator, and sensor. Values that are considered in this paper are KA = 10, KE = 1, KG = 1, KS = 1, TA = 0.1, TE = 0.4, TG = 1, and TS = 0.01 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. It is important to mention that the gain of the generator KG depends on the load of the generator.…”
Section: Component Transfer Functionmentioning
confidence: 99%
“…, and T S = 0.01 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. It is important to mention that the gain of the generator K G depends on the load of the generator.…”
Section: Component Transfer Function Range Of the Parametersmentioning
confidence: 99%
See 2 more Smart Citations